Factors affecting women's participation in soil & water conservation in abeshege district Southern Ethiopia - Tsegamariam Dula Sherka (Cogent Economics & Finance, 2023)
The primary industry in Ethiopia that makes a significant contribution to economic growth is still agriculture. Despite making a considerable contribution to livelihoods, the sector continues to encounter difficulties since soil degradation and resource depletion have decreased crop and livestock yields. To curb the effects of land degradation, the Ethiopian government has taken serious measures to expand soil and water conservation (SWC) practices across the country. Despite the efforts made, the participation of women in SWC activities has been low. The study was conducted to investigate women's participation in SWC practices in the Abeshege district of southern Ethiopia. A random sampling procedure was used to select 164 participating and 70 non-participating households from a purposively selected sample of six rural kebeles. Data were collected from both primary and secondary sources using interview designs, focus group discussions, semi-structured interviews, and discussions with key informants. The study found that women participate in various SWC practices, including agroforestry, crop rotation, waterways, stone terracing, and contour plowing, among others. The study findings suggest that education, land size, economically active household members, size of household members, and extension contact were found to significantly affect the participation of women in SWC activities. Therefore, recognize and support women's active involvement in SWC through tailored policies, programs, and initiatives that address the identified factors affecting their participation.
Keywords: 330; Ethiopia; and water conservation; probit model; soil; Women's participation